Oil Prices, Inflation and Interest Rates in a Structural Cointegrated VAR Model for the G-7 Countries - Matteo Manera; Alessandro Cologni (Fondazione Eni Enrico Mattei (FEEM), 2005)
Sharp increases in the price of oil are generally seen as a major contributor to business cycle asymmetries. Moreover, the very recent highs registered in the world oil market are causing concern about possible slowdowns in the economic performance of the most developed countries. While several authors have considered the direct channels of transmission of energy price increases, other authors have argued that the economic downturns arose from the monetary policy response to the inflation presumably caused by oil price increases. In this paper a structural cointegrated VAR model has been considered for the G-7 countries in order to study the direct effects of oil price shocks on output and prices and the reaction of monetary variables to external shocks. Empirical analysis shows that, for most of the countries considered, there seems to be an impact of unexpected oil price shocks on interest rates, suggesting a contractionary monetary policy response directed to fight inflation. In turn, increases in interest rates are transmitted to real economy by reducing output growth and the inflation rate.
Keywords: E31; E32; E52; Q41; 330; Oil price shocks; Monetary policy response; Structural VAR models; Ölpreis; Schock; Geldpolitik; VAR-Modell; G-7-Staaten